Effet du nitrate d’uranyle sur la germination des graines du Cléome amblyocarpa - MAKHLOUF, Imane; HAMOUDA, Fatima (My University, 2019)
Metal trace elements are naturally present as traces in the soil. Indeed, they are present in all compartments of the environment, but in general in very small quantities. Thus, it is useful to study the impact of heavy metal pollution on cultivated plants. In this context, we investigated the effect of uranium in the form of uranyl hexahydrate nitrate [UO2 (NO3) 2-6H2O] on the germination rate and growth of radicules and tigelles of Cleome ambryocarpa. The seeds of Cleome amblyocarpa are deposited in petri dishes (20 seeds / dish), then they are germinated in an oven at 26 ° C for 15 days. The metal stress is composed of the control solution (distilled water) accompanied by several concentrations (50, 100, 150, 200, 250 and 300 ppm of uranyl hexa hydrate nitrate). Experiments for each batch are repeated 5 times. The results obtained show that the germination rate increases under the effect of 100, 150, 200 and 250 ppm, moreover, the length of the aerial parts of the seedlings decreases under the effect of 50, 100, 200 and 300 ppm, however the elongation of the root parts is stimulated with 50, 100, 200 and 250 ppm relative to the control.
Keywords: Cleome amblyocarpa; germination; uranyl nitrate; metallic stress; phytoremediation.